Xenopus laevis P23H rhodopsin transgene causes rod photoreceptor degeneration that is more severe in the ventral retina and is modulated by light - Zhang, Rui (2008)
Rhodopsin transgenes carrying mutations that cause autosomal dominant retinitis pigmentosa in humans have been used to study rod photoreceptor degeneration in various model organisms including Xenopus laevis. To date, the only transgenes shown to cause rod photoreceptor degeneration in Xenopus laevis have been either mammalian rhodopsins or chimeric versions of rhodopsin based mainly on Xenopus laevis rhodopsin sequences but with a mammalian C-terminus. Since the C-terminal sequence of rhodopsin is highly conserved in mammals and divergent in Xenopus laevis, and mammalian and epitope-tagged rhodopsins may have unexpected properties as transgenes, we decided to test whether a Xenopus laevis rhodopsin transgence carrying only the P23H mutation could also cause rod photoreceptor degeneration. Xenopus laevis tadpoles expressing these transgenes indeed had shortened outer segments and, in severely affected animals, the loss of rod photoreceptors but not the loss of cone photoreceptors. RT-PCR analyses showed that less than 10% of mutant transgenic rhodopsin relative to wild-type endogenous rhodopsin mRNA was sufficient to produce severe rod photoreceptor degeneration. As observed in other animal models as well as humans carrying this particular rhodopsin mutation, the rod photoreceptor degeneration was most severe in the ventral retina and was modified by light. Thus, the rod photoreceptor degeneration produced in Xenopus laevis by the P23H mutation in an otherwise untagged Xenopus laevis rhodopsin is generally similar to that seen with mammalian rhodopsins and epitope-tagged versions of Xenopus laevis rhodopsin, though some differences remain to be explained.